2015
DOI: 10.3389/fmicb.2015.00907
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium ions mitigate biofilm formation of Bacillus species via downregulation of matrix genes expression

Abstract: The objective of this study was to investigate the effect of Mg2+ ions on biofilm formation by Bacillus species, which are considered as problematic microorganisms in the food industry. We found that magnesium ions are capable to inhibit significantly biofilm formation of Bacillus species at 50 mM concentration and higher. We further report that Mg2+ ions don't inhibit bacterial growth at elevated concentrations; hence, the mode of action of Mg2+ ions is apparently specific to inhibition of biofilm formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 40 publications
(55 reference statements)
1
38
0
Order By: Relevance
“…Magnesium stress, can affect many protein expression pathways related to biofilm and subsequent cellulose degradation via alternative carbohydrate utilization. While our study was focused on the effects of low magnesium stress, other studies have been able to show the same is true for environments with high (50 mM) MgSO 4 concentrations as well [35]. Oknin et al were able to show that Mg 2+ ions are specific to inhibition of biofilm formation, which depends on the maturation of the extracellular matrix.…”
Section: Relevance Of Magnesium For Biofilm and Other Cellular Functionssupporting
confidence: 50%
See 1 more Smart Citation
“…Magnesium stress, can affect many protein expression pathways related to biofilm and subsequent cellulose degradation via alternative carbohydrate utilization. While our study was focused on the effects of low magnesium stress, other studies have been able to show the same is true for environments with high (50 mM) MgSO 4 concentrations as well [35]. Oknin et al were able to show that Mg 2+ ions are specific to inhibition of biofilm formation, which depends on the maturation of the extracellular matrix.…”
Section: Relevance Of Magnesium For Biofilm and Other Cellular Functionssupporting
confidence: 50%
“…Oknin et al were able to show that Mg 2+ ions are specific to inhibition of biofilm formation, which depends on the maturation of the extracellular matrix. This is controlled by the epsA-O and tapA operons, and linked to the gene expression of β-galactosidase [35,36]; a connection between biofilm and cellulase production. Mg 2+ ions play a key role in the growth and metabolic functions of bacteria.…”
Section: Relevance Of Magnesium For Biofilm and Other Cellular Functionsmentioning
confidence: 99%
“…One milliliter of each sample was collected and centrifuged at 5000 rpm for 2 min. The supernatant was discarded, the pellet was re-suspended and 3 μl of the suspension placed on a glass slide was visualized in a transmitted light microscope using Nomarski differential interference contrast (DIC), at 40× magnification ( Pasvolsky et al, 2014 ; Oknin et al, 2015 ). Furthermore, a confocal laser scanning microscope (CLSM) was used to visualize cyan fluorescent protein (CFP) or green fluorescent protein (GFP) expression.…”
Section: Methodsmentioning
confidence: 99%
“…55 There are no systematic studies about the effect of bacteria on the degradation of Mg or the composition of the degradation layer. This is partially caused by the antimicrobial effect of fast degrading Mg alloys 56 or because Ag or Zn were used as alloying elements. 57,58 On the other hand, it is reported that, on slowly degrading Mg-based materials, bacteria can survive very well, 59 although the degradation layer is then so thin that its analysis is challenging.…”
Section: Degradation In Presence Of Cellsmentioning
confidence: 99%